PERAN BANK INDONESIA TERHADAP PELAKSAANAN KLIRING DALAM EFEKTIVITAS SISTEM PEMBAYARAN ANTAR BANK - Hutagalung, Piana Winsky; Damanik, Hotraniati; Br Tohang, Uli Nurhaida; Siallagan, Hamonangan; Hasugian, Chrisnova (Jurnal Akuntansi Kompetif, 2025)
This Scientific work the role of Bank Indonesia in the implementation of clearing and the effectiveness of interbank payment systems. Using a descriptive qualitative approach, this research aims to identify and analyze how Bank Indonesia contributes to enhancing customer trust in the payment system. The study also explores the procedures for clearing organized by Bank Indonesia and the effectiveness of the policies implemented. Through literature review and document analysis, this paper concludes that the strategic role of Bank Indonesia is crucial in maintaining the stability of the payment system, and it provides recommendations for better monetary policy development in the future. It is hoped that the findings of this research can provide in-depth insights for policymakers and practitioners in the banking sector.